Digital Economic Transformation: In-depth Analysis of Smart Economy in the Implementation of Smart Village in Ketapang Village - Adinda Rizka Amalia; Vidya Imanuari Pertiwi (Jurnal Ad'ministrare, 2023)
Weak technology and lack of human resources caused global e-government to show that Indonesia is below the world average. It is challenging for Indonesia to have an E-Government initiative program towards Good Governance, one of which is Smart City innovation. The community economy is crucial in determining community welfare in moving towards a Smart City. With a Smart Village in Ketapang Village, Banyuwangi Regency, it is hoped that it can create community welfare through a Smart Economy. This research aims to determine the success of Smart Economy in implementing Smart Village in Ketapang Village, Banyuwangi Regency. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out using observation, interviews and documentation. If the previous research only discussed Smart Cities in general, then in this research, the author examines one of the success factors of smart cities, namely, the Smart Economy. This update discusses the Smart Economy in depth. The study was carried out based on seven Smart Economy indicators using the Giffinger approach. The research results obtained show that the Smart Economy in Ketapang Village has not been maximized due to several obstacles, such as the uneven distribution of facilities provided by the regional government, the lack of ability of the Ketapang Village community to utilize technology, and the lack of government support for technology weak responsibility towards society. However, in general, its implementation is exemplary, manifested in developing technological innovations for the community and government facilities that continue to be built.